2013
DOI: 10.1007/s40003-013-0068-4
|View full text |Cite
|
Sign up to set email alerts
|

Authentication of Mango Varieties Using Near-Infrared Spectroscopy

Abstract: Mango cultivars are presently identified phenotypically. In the present study, near-infrared spectroscopy in the wavelength range of 1,200-2,200 nm, in combination with chemometrics was evaluated for the purpose. Principal component analysis and partial least square (PLS) discriminate analysis were applied using characteristic variables as 0 and 1 for cv Alphonso and Banganapalli, respectively, in one group and for Dasheri and Malda, respectively, in the other group. PLS was carried out with and without pre-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Their findings showed that overall, NNs perform best at the task. Neural networks were also employed in [17] to forecast monthly wholesale prices of two agricultural products. Ahumada and Cornejo [18] considered a similar problem, also taking into account possible cross-dependencies of different product prices.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings showed that overall, NNs perform best at the task. Neural networks were also employed in [17] to forecast monthly wholesale prices of two agricultural products. Ahumada and Cornejo [18] considered a similar problem, also taking into account possible cross-dependencies of different product prices.…”
Section: Introductionmentioning
confidence: 99%
“…Spectroscopy is a non-destructive, inexpensive, rapid and reliable technique that has traditionally been used in food chemistry for qualitative and quantitative determination of different compounds in fruit samples, especially near infrared (NIR) spectroscopy (Nicolaï et al, 2007;Nicolaï et al, 2014;Magwaza et al, 2012;López et al, 2013). This technique has been utilised for the quantitative determination of soluble solids content (SSC), firmness, acidity, dry matter, chemical substances such as glucose, sucrose, citric acid, malic acid, starch or cellulose in different fruits (Schmilovitch et al, 2000;Nagle et al, 2010;Theanjumpol et al, 2013), and even to determine a maturity index (Jha et al, 2013), internal quality index (Cortés et al, 2016) or different appropriate indices for quality analysis (Attila and János, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…More sophisticated approaches are based on neural networks methods, etc. [11]. Another approach is to use structural models [12].…”
Section: Introductionmentioning
confidence: 99%